STUDY OF RISK FACTORS AND RATE OF IN-STENT RESTENOSIS IN PATIENTS UNDERGOING PERCUTANEOUS CORONARY INTERVENTION (PCI) WITH DRUG-ELUTING STENTS (DES) (The Research of Medical Science Review, 2024)
Introduction: In-stent restenosis (ISR) remains a significant clinical concern for patients undergoing percutaneous coronary intervention (PCI), despite the use of advanced drugeluting stents (DES). Objective: The main objective of the study is to find the risk factors and rate of in-stent restenosis in patients undergoing PCI with DES. Methodology: This retrospective observational study was conducted at Hayatabad Medical Complex in Peshawar from January 2019 to December 2020. A total of 85 patients who underwent PCI with DES during this period were included in the study. Results: Out of the 85 patients with a majority of 58 males (68.2%) and 27 females (31.8%). The mean age of the patients was 61.4 ± 9.3 years. Nearly half of the patients (47%) had diabetes mellitus, and 61% had a history of hypertension. Chronic kidney disease was present in 14% of the patients, while 27% were identified as active smokers. Diabetes mellitus was more prevalent in the ISR group (66.7%) compared to the non-ISR group (43.8%). Likewise, hypertension was more common in the ISR group (75%) than in the non-ISR group (58.9%). Chronic kidney disease was also more frequent in the ISR group (25% vs. 12.3%). Conclusion: It is concluded that in-stent restenosis (ISR) remains a significant clinical issue in patients undergoing PCI with drug-eluting stents (DES), particularly in those with diabetes, complex lesions, and small vessel diameters.